(untitled) (Global Journal of Management and Business Research, 2017)
The present study aims to understand the brand related content generated by internet users on social media and its influence on the consumer-based brand equity constructs. The dimensions of consumer-based brad equity considered in the study are based on the Aaker Brand Equity model, and Facebook, being the mostly accessed site, is considered for study. For the above mentioned objective, the data has been gathered from 500 respondents, using a wellstructured questionnaire. The respondents comprise people within the age group of 18-35 years. The findings reveal a significant impact of user-generated content on brand equity constructs and have implications for brand managers and media planners for administering the usergenerated content on social media, and also for various researchers and academicians towards examining the effects of such social interactions on brand elements.